PENGARUH PENERAPAN PAIKEM DALAM MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERTUKAR PASANGAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMP NEGERI 2 BAYANG TAHUN PELAJARAN 2012/2013 - Putri, Anika; Rismen, Sefna; Anggraini, Villia (Pendidikan Matematika, 2013)
This research background for the understanding of mathematical concepts students are low and students do not want the beta to the teacher and told friends what they do not understand about the subject matter being studied. The research aims to determine whether the students understanding of mathematical concepts by applying PAIKEM in cooperative learning model couples swapping technique is better than the students understanding of mathematical concepts with conventional learning in class IX SMP 2 Imagine the school year 2012/2013 .This type of research is experimental , with random design of the subject . The population in this study were all students of class IX SMP 2 Bayang listed in the school year 2012/2013 . Sampling was done randomly so that the selected class as a class ix2 XI6 as experimental and control classes . The instrument used was a test of understanding the concept in the form of essays with reliability 0 , 80.Teknik analysis of the data used is the t test with one hand calculation MINITAB software .Based on the analysis of data obtained average value of mathematics learning outcomes experimental class is 85,30 and control class 79.14. Hypothesis testing using t-test with a one -party software MINITAB calculations obtained p - value 0.037 and Î± = 0.05 means p - value < Î± then the hypothesis is accepted at the 95% confidence level . It can be concluded that the students understanding of mathematical concepts in mathematics learning by applying PAIKEM in the cooperative learning technique Couple Exchanging better than the students understanding of mathematical concepts by applying conventional learning models in class IX SMP 2 Imagine the school year 2012/2013 .